Qualitätsentwicklung im Unterricht – zur Rolle digitaler Medien - Eickelmann, Birgit; Schulz-Zander, Renate (Jahrbuch der Schulentwicklung. Daten, Beispiele und Perspektiven/Jahrbuch der Schulentwicklung)

Individualisieren mit digitalen Medien – ein zeitgemäßer Beitrag zur Verbesserung von Unterrichtsqualität - Eickelmann, Birgit (Unterrichtsqualität sichern – Sekundarstufe)

Unterricht individualisieren – mit Computer und Internet - Eickelmann, Birgit (Unterrichtsqualität sichern – Grundschule)

Das Globale-Schule-System - eine Handlungsalternative im Distance Learning für das deutsche Auslandsschulwesen - Eickelmann, Birgit

Vorwort zum Track Integriertes Ertrags-/Risikomanagement in automatisierten Geschäftsprozessen - Müller, G.; Kundisch, Dennis; Sackmann, S.; Romeike, F.

Negotiating identities through pronouns of address in an immigrant community - Liebscher, Grit; Dailey-O’Cain, Jennifer; Müller, Mareike; Reichert, Tetyana (Pragmatics. Quarterly Publication of the International Pragmatics Association (IPrA))
This article investigates forms of address, in particular the T/V distinction in German, in conversational interviews with German-speaking immigrants to English-speaking Canada and their descendants. From among 77 interviews conducted in two urban areas in Canada, we discuss instances of both the interactional use of and metalinguistic comments on forms of address. Our analysis is largely guided by conversation analysis and interactional sociolinguistics (e.g. Goodwin & Heritage 1990). Using Clyne, Norrby and Warren’s (2009) model of address as a backdrop, we investigate the construction of group identity and group socialization through the lens of positioning theory (e.g. van Langenhove & Harré 1993; Dailey-O’Cain & Liebscher 2009). This combination of analytical tools can explain shifts in both usage of and attitudes toward the T/V distinction that cannot be explained through language attrition arguments alone.
Keywords: Forms of address; T/V distinction; Du vs. Sie; Conversation analysis; Language attitudes; Interviews; German in Canada; Migration studies; North American migration

Robust Undetectable Interference Watermarks - Grza̧ślewicz, Ryszard; Kutyłowski, Jarosław; Kutyłowski, Mirosław; Pietkiewicz, Wojciech (ICCSA'05: Proceedings of the 2005 international conference on Computational Science and Its Applications)

An investigation of doubly-resonant optical parametric oscillators and nonlinear crystals for squeezing - Stefszky, Michael; Mow-Lowry, Conor M; McKenzie, Kirk; Chua, Sheon; Buchler, Ben C; Symul, Thomas; McClelland, David E; Lam, Ping Koy (Journal of Physics B: Atomic, Molecular and Optical Physics)

Lebenszyklusorientierte Investitionsplanung - Betz, Stefan (Der Betrieb)

Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 2: Theoretical analysis of the formation mechanism - Körmer, R.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
This work investigates the mechanisms which lead to the formation of silicon nanoparticles with narrow size distributions by means of population balance modeling. The model accounts for the full aerosol process, including chemical reaction, nucleation from supersaturated vapor, growth and agglomeration. The results are in good agreement with experimental data. The effects of the process parameters temperature, silane concentration and reactor total pressure are systematically investigated. The simulation allows an in-depth insight into the particle formation mechanism and reveals the key requirements which are necessary for the generation of narrow particle size distributions. In this mechanism, only a short nucleation burst occurs, while surface growth plays the dominant role in silane precursor consumption. A key role is attributed to condensation, because the numerical calculations can only reflect the experimental observations, if the condensation mechanism is included in the model.

Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 1: Experimental investigations - Körmer, R.; Jank, M.P.M.; Ryssel, H.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
A study on the feasibility of aerosol processing of nearly monodisperse silicon nanoparticles via pyrolysis of monosilane in a hot wall reactor is presented. For optimal conditions silicon nanoparticles with a geometric standard deviation of 1.06 were synthesized at a production rate of 0.7 g/h. The size of the particles could be precisely controlled in the range of 20–40 nm, whilst maintaining a geometric standard deviation in the range of 1.06–1.08, by proper choice of the governing parameters temperature, residence time and precursor concentration. The results show that narrow particle size distributions can only be obtained in the temperature range between 900 and 1100 °C, as long as both the initial silane concentration (1 mbar silane partial pressure) and the reactor total pressure are low (25 mbar). This regime for the production of narrow particle size distributions has not been identified in prior work on the thermal decomposition of silane. Narrowly distributed particles can be obtained under conditions where nucleation and particle growth are separated and the agglomeration rates are negligible.

Interparticle forces in silica nanoparticle agglomerates - Seipenbusch, M.; Rothenbacher, S.; Kirchhoff, M.; Schmid, Hans-Joachim; Kasper, G.; Weber, A. P. (Journal of Nanoparticle Research)
To improve the understanding of the poor dispersability of fumed silica nanoparticle agglomerates, the stability of highly defined agglomerated model particles was investigated. The high temperature synthesis conditions for fumed silica were simulated by tempering. Along with electron-microscopical analysis of the sintering necks, the interparticle forces were investigated by energy resolved fragmentation analysis based on low pressure impaction. At temperatures above 1,000 °C the fragmentability of the agglomerates rapidly decreased while the energy necessary for fragmentation increased. The development of sintering necks was observed for temperatures exceeding 1,300 °C. Comparison of the experimental data with the fragmentation behaviour of a commercially produced fumed silica indicated solid state contacts (sintering necks) as being most numerous in the agglomerates resulting in limited fragmentability.

Verfahren zur integrierten informationstechnischen Unterstützung des Innovationsmanagements - Ihmels, Stephan

7. Paderborner Workshop Entwurf mechatronischer Systeme - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm; Trächtler, Ansgar

Run-time Reconfigurable Multiprocessors - Purnaprajna, Madhura

Lebensdauerüberwachung in mechatronischen Systemen - Wedman, Sebastian

6. Symposium für Vorausschau und Technologieplanung - Gausemeier, Jürgen

Systematik zur funktionsorientierten Modellierung von Elektrik/ Elektronik-Systemen über den Produktlebenszyklus - Warkentin, Andreas

Adaptable OS services for distributed reconfigurable systems on chip - Samara, Sufyan

On the design and implementation of reliable and economical telematics software architectures for embedded systems : a domain-specific framework - Stehr, Jan

Price Efficiency in Futures and Spot Trading: The Role of Information Technology - Wagener, Martin; Kundisch, Dennis; Riordan, R.; Rabhi, Fethi; Herrmann, Philipp; Weinhardt, C. (Electronic Commerce Research and Applications)

Characterizing nonclassicality and entanglement - Vogel, W.; Kiesel, T.; Sperling, Jan (Optics and Spectroscopy)

Customer Portfolio Management in E-Commerce - An Analytical Model for Optimization - Sackmann, S.; Kundisch, Dennis; Ruch, M. (Management Research Review)

A User-Driven SOA for Financial Market Data Analysis - Guabtni, A.; Kundisch, Dennis; Rabhi, Fethi (Enterprise Modelling and Information Systems Architectures)

Der Einfluss von Sozialkapital in der Asset Allocation von Privatanlegern - Kundisch, Dennis; Zorzi, R. (Journal of Banking and Financial Research)

Einfluss der Finanzierung auf die Steuerbarkeit und Vorteilhaftigkeit von Investitionen - Kundisch, Dennis; Satzger, G. (Der Betrieb)

Dirac point and edge states in a microwave realization of tight-binding graphene-like structures - Kuhl, U.; Barkhofen, Sonja; Tudorovskiy, T.; Stöckmann, H.-J.; Hossain, T.; de Forges de Parny, L.; Mortessagne, F. (Physical Review B)

Einführung in den Anfangsunterricht - Hellmich, Frank

Handbuch Experimentieren.

Geschlechtsspezifische Unterschiede in der Lesekompetenz bei Grundschulkindern im Zusammenhang mit pädagogisch-didaktischen Überzeugungen ihrer Lehrkräfte - Hellmich, Frank; Höntges, Jens; Günther, Frederike (Erziehungswissenschaftliche Forschung – nachhaltige Bildung)

Attributionsstile von Grundschulkindern und deren Erklärungsfaktoren - Hellmich, Frank; Günther, Frederike; Sievers, Sebastian (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik. Jahrbuch Grundschulpädagogik)

Attributionsstile von Grundschulkindern und deren Erklärungsfaktoren - Deters, Thomas; Hellmich, Frank (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik.)

Förderung der Lesefähigkeit durch Lesetagebücher – Ergebnisse aus einer empirischen Studie - Höntges, Jens; Hellmich, Frank (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik)

Wissenschaftliches Denken in der Grundschule - Hellmich, Frank; Höntges, Jens (Handbuch Experimentieren)

Glück oder Pech? Über Erfolge und Misserfolge nachdenken – eine Herausforderung für Kinder?! - Deters, Thomas; Hellmich, Frank (Grundschulunterricht)

Diagnose und Förderung im Mathematikunterricht der Grundschule - Hellmich, Frank (Anspruchsvolles Fördern in der Grundschule)

Erklärungsfaktoren für dynamische Selbstkonzepte bei Grundschulkindern - Hellmich, Frank; Günther, Frederike; Sievers, Sebastian (Zwischen Fachdidaktik und Stufendidaktik: Perspektiven für die Grundschulpädagogik)

Validation of protein intake assessed from weighed dietary records against protein estimated from 24 h urine samples in children, adolescents and young adults participating in the Dortmund Nutritional and Longitudinally Designed (DONALD) Study - Bokhof, Beate; Günther, Anke LB; Berg-Beckhoff, Gabriele; Kroke, Anja; Buyken, Anette (Public Health Nutrition)

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

Relation of isoflavones and fiber intake in childhood to the timing of puberty - Cheng, Guo; Remer, Thomas; Prinz-Langenohl, Reinhild; Blaszkewicz, Meinolf; Degen, Gisela H; Buyken, Anette (The American Journal of Clinical Nutrition)

A CSP Approach to Control in Event-B - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Integrated Formal Methods - 8th International Conference, IFM 2010, Nancy, France, October 11-14, 2010. Proceedings)

{SLAB:} A Certifying Model Checker for Infinite-State Concurrent Systems - Dräger, Klaus; Kupriyanov, Andrey; Finkbeiner, Bernd; Wehrheim, Heike (Tools and Algorithms for the Construction and Analysis of Systems, 16th International Conference, TACAS 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings)

Towards A Shape Analysis for Graph Transformation Systems - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (CoRR)

Survival at the center—the stability of minimum differentiation - Hehenkamp, Burkhard; Wambach, Achim (Journal of Economic Behavior & Organization)

Produktivitätsbenchmarking als Bestandteil eines integrierten Ansatzes zur Vermarktung hybrider Leistungsbündel - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Broeker, Ole; Knackstedt, Ralf; Nikula, Anna; Wilken, Robert (40. Jahrestagung der Gesellschaft für Informatik)

Incorporating Willingness-to-Pay Data into Online Recommendations for Value-Added Services - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Frohs, Margarete; Müller, Oliver; Weddeling, Matthias (European Conference on Information Systems)

Produktivitätsmanagement hybrider Leistungsbündel --- Auf dem Weg zu einer Produktivitätsmanagementsystematik für effiziente Wertschöpfungspartnerschaften - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Fellmann, Michael; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver (Proceedings of the Multikonferenz Wirtschaftsinformatik)

Assumptions in Service Research --- A Multi-Theoretical Perspective on the Development of Standards for the Integration of Goods and Services - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Nüttgens, Markus (XX. International RESER Conference)

Total Cost of Service Life --- Decision Support for Selecting and Orchestrating Services - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the IADIS Internatioal Conference e-Society 2010)

Total Costs of Service Life: The Need of Decision Support in Selecting, Comparing and Orchestrating Services - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Exploring Service Sciences)

Implementing Value-Driven Service Management --- Towards an IT Artifact-Based Approach for Managing Customer Solutions - Beverungen, Daniel (Proceedings of the 10th European Academy of Management Conference)

Enabling Individualized Recommendations and Dynamic Pricing of Value-Added Services through Willingness-to-Pay Data - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Frohs, Margarethe; Müller, Oliver; Weddeling, Matthias; Knackstedt, Ralf; Steiner, Michael (Electronic Markets)

The Challenge of Conceptual Modeling for Product-Service Systems --- Status-quo and Perspectives for Reference Models and Modeling Languages - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Information Systems and e-Business Management (ISeB))

Fostering the Virtualization of Service Processes and Touch Points --- Identification and Documentation of E-Service Potential in Retail Networks - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (Lecture Notes in Informatics)

Expertise of team leaders in analysing team conflicts - Rupprecht, Maria; Strasser, Josef; Gruber, Hans; Harteis, Christian (Vocations and Learning)

How Epistemic Beliefs Influence e-Learning in Daily Work-life. - Harteis, Christian; Gruber, Hans; Hertramph, Herbert (Journal of Educational Technology & Society)

Contributions of e-collaborative knowledge construction to professional learning and expertise - Harteis, Christian (Organizational Learning and Knowledge: Concepts, Methodologies, Tools and Applications)

Kompetenzerwerb im betrieblichen Arbeitsalltag - Harteis, Christian; Gruber, Hans; Rehrl, Monika (Bildungspsychologie)

Mögliche Fallstricke einer Optimierung unternehmerischer Investitionsentscheidungen auf der Grundlage der Konzernsteuerquote - Müller, Jens; Sureth, Caren; Christian, Läufer
Die Konzernsteuerquote ist ein Effektivsteuersatz, der in der jüngsten Vergangenheit aufgrund der Pflicht zur Veröffentlichung dieser Kennzahl im Jahresabschluss für kapitalmarktorientierte Unternehmen immer mehr in den Blickpunkt unternehmerischen Handelns gerückt ist. Um das durch die Konzernsteuerquote an den Kapitalmarkt gesendete Signal zu optimieren, berücksichtigen einige Unternehmen die Auswirkungen ihrer Investitionsentscheidungen auf diese Kennzahl explizit in ihrer Investitionsplanung. Unter Rückgriff auf ein Simulationsmodell auf Basis vollständiger Finanzpläne wird im Rahmen einer ökonomischen Untersuchung deutlich, welche Parameter besonders großen Einfluss auf die Konzernsteuerquote haben und unter welchen Bedingungen eine sich an üblichen Renditemaßen orientierende Investitionspolitik unzureichend dargestellt wird. Es zeigt sich, dass der in der Praxis verbreitete Rückgriff auf die Konzernsteuerquote als Performance- Kennzahl ohne entsprechende Informationsarbeit zu fehlerhaften und unerwünschten Beurteilungen der unternehmerischen Steuerpolitik führen kann.
Keywords: Konzernsteuerquote; Investitionsentscheidungen

Wirtschaft und Betrieb - Heid, Helmut; Harteis, Christian (Handbuch Bildungsforschung)

Efficient Statement Identification for Automatic Market Forecasting - Wachsmuth, Henning; Prettenhofer, Peter; Stein, Benno (Proceedings of the 23rd International Conference on Computational Linguistics (Coling 2010))

Teacher Professional Development - An Empirical Analysis of ICT-related Teacher Cooperation from a School Improvement Perspective - Schulz-Zander, Renate; Eickelmann, Birgit (Proceedings of 21st International Conference of SITE (Society for Information Technology & Teacher Education))

Factors Contributing to a Sustainable Implementation of Digital Media in Schools and Classrooms – Empirical Analyses and some Consequences for Teacher Education - Eickelmann, Birgit (Proceedings of 21st International Conference of SITE (Society for Information Technology & Teacher Education))

Digitale Medien in Schule und Unterricht erfolgreich implementieren - Eickelmann, Birgit

Das Globale-Schule-System – Evaluation einer Handlungsalternative im Distance Learning für das deutsche Auslandsschulwesen - Eickelmann, Birgit

Bregman Clustering for Separable Instances - Ackermann, Marcel R.; Blömer, Johannes (SWAT 2010)

Clustering for Metric and Nonmetric Distance Measures - Ackermann, Marcel R.; Blömer, Johannes; Sohler, Christian (ACM Trans. Algorithms)
Keywords: k-means clustering; k-median clustering; Approximation algorithm; Bregman divergences; Itakura-Saito divergence; Kullback-Leibler divergence; Mahalanobis distance; random sampling

On the initialization of dynamic models for speech features - Krueger, Alexander; Leutnant, Volker; Haeb-Umbach, Reinhold; Ackermann, Marcel; Blömer, Johannes (Proc. of ITG Fachtagung Sprachkommunikation. ITG, Bochum, Germany)

Efficient and Compact CCA Security from Partitioned IBKEM - Schrieb, Jonas

Engineering self-coordinating software intensive systems - Schäfer, Wilhelm; Trächtler, Ansgar; Birattari, Mauro; Blömer, Johannes; Dorigo, Marco; Engels, Gregor; O'Grady, Rehan; Platzner, Marco; Rammig, Franz; Reif, Wolfgang (Proceedings of the FSE/SDP workshop on Future of software engineering research - FoSER '10)

Entrepreneurship and Structural Economic Transformation - Gries, Thomas; Naudé, Wim (Small Business Economics)

Generic Compilers for Authenticated Key Exchange - Jager, Tibor; Kohlar, Florian; Schäge, Sven; Schwenk, Jörg (Advances in Cryptology - ASIACRYPT 2010 - 16th International Conference on the Theory and Application of Cryptology and Information Security, Singapore, December 5-9, 2010. Proceedings)

The Semi-Generic Group Model and Applications to Pairing-Based Cryptography - Jager, Tibor; Rupp, Andy (Advances in Cryptology - ASIACRYPT 2010 - 16th International Conference on the Theory and Application of Cryptology and Information Security, Singapore, December 5-9, 2010. Proceedings)

Simple and Efficient Public-Key Encryption from Computational Diffie-Hellman in the Standard Model - Haralambiev, Kristiyan; Jager, Tibor; Kiltz, Eike; Shoup, Victor (Public Key Cryptography - PKC 2010, 13th International Conference on Practice and Theory in Public Key Cryptography, Paris, France, May 26-28, 2010. Proceedings)

Model transformations across views - Derrick, John; Wehrheim, Heike (Sci. Comput. Program.)

Model-Driven Development with Mechatronic UML - Schäfer, Wilhelm; Wehrheim, Heike (Graph Transformations and Model-Driven Engineering - Essays Dedicated to Manfred Nagl on the Occasion of his 65th Birthday)

On Symmetries and Spotlights - Verifying Parameterised Systems - Timm, Nils; Wehrheim, Heike (Formal Methods and Software Engineering - 12th International Conference on Formal Engineering Methods, ICFEM 2010, Shanghai, China, November 17-19, 2010. Proceedings)

Showing Full Semantics Preservation in Model Transformation - A Comparison of Techniques - Hülsbusch, Mathias; König, Barbara; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike (Integrated Formal Methods - 8th International Conference, IFM 2010, Nancy, France, October 11-14, 2010. Proceedings)

Carbohydrate nutrition and inflammatory disease mortality in older adults - Buyken, Anette; Flood, Victoria; Empson, Marianne; Rochtchina, Elena; Barclay, Alan W; Brand-Miller, Jennie; Mitchell, Paul (The American Journal of Clinical Nutrition)

Convenience foods in children's diet and association with dietary quality and body weight status - Alexy, U; Libuda, Lars; Mersmann, S; Kersting, M (European Journal of Clinical Nutrition)

Comparison of the effects of dietary protein, androstenediol and forearm muscle area on radial bone variables in healthy prepubertal children - Libuda, Lars; Wudy, Stefan A.; Schoenau, Eckhard; Remer, Thomas (British Journal of Nutrition)
Adequate dietary habits are supposed to be one of the most important modifiable factors in osteoporosis prevention. However, the importance of specific nutrients is controversial. We examined relevant nutrients which are supposed to have an impact on bone parameters and compared their effect sizes with those of two known predictors of bone development: bone-related muscle mass and androgen levels. We analysed nutritional, hormonal and anthropometric data from 107 prepubertal children participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed Study. Diaphyseal bone mineral content (BMC), cortical area (CA), periosteal circumference, strength strain index and muscle area of the non-dominant forearm were measured by peripheral quantitative computed tomography. Data on long-term nutrient intakes (e.g. protein, Ca and vitamin D) were derived from 3 d weighed dietary records. Twenty-four hour urinary excretion rates of androgen metabolites including the sex steroid androstenediol were measured using GC–MS. Of all considered nutrients, only protein showed a trend for an association with BMC (β = +0·11; P = 0·073) and CA (β = +0·11; P = 0·056) in stepwise linear regression models. None of the other considered dietary variables was associated with bone parameters. The size of the bone anabolic effect of protein was partly comparable with that of androstenediol. Even though boys gained more bone mass in comparison with girls, the protein effect did not differ between sexes. Bone-related muscle area and sex steroids have the strongest effects on prepubertal diaphyseal bone. However, dietary protein may have a similar bone anabolic influence compared with androstenediol. In children without explicit nutrient deficits, protein seems to be the most important dietary component for diaphyseal bone status.

Urinary fructose: a potential biomarker for dietary fructose intake in children - Johner, S A; Libuda, Lars; Shi, L; Retzlaff, A; Joslowski, G; Remer, T (European Journal of Clinical Nutrition)

Longitudinal Associations between Endogenous Melatonin Production and Reported Sleep Duration from Childhood to Early Adulthood - Diethelm, Katharina; Libuda, Lars; Bolzenius, Katja; Griefahn, Barbara; Buyken, Anette; Remer, Thomas (Hormone Research in Paediatrics)

Real-time Adaptation and Load Balancing Aware OS Services for Distributed Reconfigurable System on Chip - Samara, Sufyan; Schomaker, Gunnar (2010 10th IEEE International Conference on Computer and Information Technology)

Short-run and Long-run Dynamics of Growth,Inequality and Poverty in the Developing World - Gries, Thomas; Redlin, Margarete

Bone-anabolic impact of dietary high protein intake compared with effects of low potential renal acid load, endogenous steroid hormones, and muscularity in children. - Remer, T.; Libuda, Lars (Nutritional Influences on Bone Health.)

Prepubertal Adrenarchal Androgens and Animal Protein Intake Independently and Differentially Influence Pubertal Timing - Remer, Thomas; Shi, Lijie; Buyken, Anette; Maser-Gluth, Christiane; Hartmann, Michaela F.; Wudy, Stefan A. (The Journal of Clinical Endocrinology & Metabolism)

Prepubertal urinary estrogen excretion and its relationship with pubertal timing - Shi, Lijie; Remer, Thomas; Buyken, Anette; Hartmann, Michaela F.; Hoffmann, Philipp; Wudy, Stefan A. (American Journal of Physiology-Endocrinology and Metabolism)
Whether prepubertal estrogen production impacts on the timing of puberty is not clear. We aimed to investigate prepubertal 24-h estrogen excretion levels and their association with early and late pubertal markers. Daily urinary excretion rates of estrogens of 132 healthy children, who provided 24-h urine samples 1 and 2 yr before the start of the pubertal growth spurt [age at takeoff (ATO)], were quantified by stable isotope dilution/GC-MS. E-sum3 (estrone + estradiol + estriol) was used as a marker for potentially bioactive estrogen metabolites and E-sum5 (E-sum3 + 16-epiestriol + 16-ketoestradiol) for total estrogen production. Pubertal outcomes were ATO, age at peak height velocity (APHV), duration of pubertal growth acceleration (APHV-ATO), age at Tanner stage 2 for pubic hair (PH2), genital (G2, boys) and breast (B2, girls) development, and age at menarche. Prepubertal urinary estrogen excretions (E-sum3 and E-sum5) were not associated with ATO, APHV, and age at PH2 but with duration of pubertal growth acceleration ( P < 0.01) in both sexes. Girls with higher E-sum3 reached B2 0.9 yr ( P = 0.04) and menarche 0.3 yr earlier ( P = 0.04) than girls with lower E-sum3. E-sum3 was not associated with age at G2 in boys ( P = 0.6). For most pubertal variables, the associations with E-sum3 were stronger than with E-sum5. In conclusion, prepubertal estrogens may not be critical for the onset of the pubertal growth spurt but are correlated with its duration in both boys and girls. Prepubertal estrogen levels may already predict the timing of girls' menstruation and breast development but do not appear to affect sexual maturation in boys.

Body composition trajectories into adolescence according to age at pubertal growth spurt - Buyken, Anette; Bolzenius, Katja; Karaolis-Danckert, Nadina; Günther, Anke L.B.; Kroke, Anja (American Journal of Human Biology)

A Sequential Model for Global Spam-Classifying Processes - Burkart, W.; Etschberger, S.; Klein, C.; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

Optimal dietary approaches for prevention of type 2 diabetes: a life-course perspective - Buyken, Anette; Mitchell, P.; Ceriello, A.; Brand-Miller, J. (Diabetologia)

Urinary isoflavone phytoestrogens in German children and adolescents - A longitudinal examination in the DONALD cohort - Degen, Gisela H.; Blaszkewicz, Meinolf; Shi, Lijie; Buyken, Anette; Remer, Thomas (Molecular Nutrition & Food Research)

Explaining the Trading Venue Decision of Private Online Investors - An Empirical Study - Herrmann, Philipp; Kundisch, Dennis (International Workshop on Enterprise Applications, Markets and Services in the Finance Industry (FinanceCom))

Project interactions in value based IT project portfolio management - Meier, Christian; Kundisch, Dennis (Proceedings der GI-Jahrestagung Informatik 2010)

Sustainable Process Management - Status Quo and Perspectives - Kundisch, Dennis; Herrmann, Philipp; Meier, Christian (Proceedings of the 8th International Heinz Nixdorf Symposium (IHNS))

Mispricing and Exchange Market Systems: The Effect of Infrastructure Upgrades - Wagener, M.; Kundisch, Dennis; Riodan, R.; Rabhi, Fethi; Weinhardt, C. (Proceedings of the 43rd Hawaii International Conference on System Sciences (HICSS))

9. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, M.

BiographIE - Biographical Information Extraction from Business News - Geierhos, Michaela; Blanc, Olivier (Actes du 27e Colloque international sur le lexique et la grammaire (L’Aquila, 10-13 septembre 2008))

BiographIE - Klassifikation und Extraktion karrierespezifischer Informationen - Geierhos, Michaela
Das wesentliche Ziel der vorliegenden Publikation ist die Erstellung von sprachspezifischen Modulen im Bereich der Biographischen InformationsExtraktion (BiographIE). Unter Informationsextraktion verstehen wir die automatisierte Analyse von Dokumenten im Hinblick auf das Entdecken und Normalisieren von semantisch interessanten Entitäten und deren Eigenschaften. Das Hauptgewicht der Arbeit liegt auf sehr detaillierten und umfangreichen linguistischen Grammatiken im Bereich der Beschreibung von Personen und deren Beziehungen zu anderen relevanten Entitäten (z.B. Organisationen, Orte, Datums- und Zeitangaben) in Texten. Neben den öffentlichen und privaten Eigenschaften von Personen (Geburtsdatum, Nationalität etc.) sollen vor allem alle biographisch relevanten Attribute aus Texten extrahiert werden können. Dazu gehören in erster Linie berufliche Werdegänge, Anstellungsverhältnisse, Rollen in Firmen und ähnliche Eigenschaften. Da alle diese Attribute in unzählbar verschiedenen Formen ausgedrückt werden können, müssen sehr umfangreiche Lexika und sehr detaillierte grammatische Beschreibungen erstellt werden. Dies geschieht hauptsächlich bei der systematischen Evaluierung von Korpora. Je umfangreicher diese sind, desto adäquater werden die erstellten Grammatiken sein. Im Gegensatz zu den heute üblichen statistischen, auf maschinellem Lernen basierenden Verfahren setzen wir auch umfangreiche semi-automatisch erstellte, linguistische Module ein, die dann durch systematische Evaluierung auf Korpora schnell ergänzt und verbessert werden können. Basierend auf unseren Extraktionsmethoden ist es nun möglich, im Bereich der semantischen Suche deutliche Fortschritte zu machen. Insbesondere Personensuchmaschinen können sich unsere detaillierten Analysemethoden zu Nutze machen, um beispielsweise zu ermitteln, wer in welcher Funktion bei welcher Firma von wann bis wann beschäftigt war.
Keywords: Natural Language Processing

Reverse Engineering with the Reclipse Tool Suite - von Detten, Markus; Meyer, Matthias; Travkin, Dietrich (Proceedings of the 32nd ACM/IEEE International Conference on Software Engineering (ICSE 2010), Cape Town, South Africa, May 2-8, 2010)